2020
DOI: 10.1016/j.enganabound.2020.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Fluid-elastic structure interaction simulation by using ordinary state-based peridynamics and peridynamic differential operator

Abstract: The fluid-structure interaction phenomenon is often encountered in the ocean engineering field.In the present work, a non-local numerical model is developed for the simulations of weakly compressible viscous fluid and elastic structure interactions. The peridynamic theory is adopted for both the structure and fluid modelling. The elastic structure is described by using the ordinary state-based peridynamics, while the fluid is modelled by utilizing the peridynamic differential operator. Furthermore, the updated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 69 publications
(112 reference statements)
0
3
0
Order By: Relevance
“…13 Yan et al 21,22 further developed a higher order nonlocal operators for the updated Lagrangian particle hydrodynamics and used them to study and simulate multiphase fluid flow problems. Gao and Oterkus 23 developed a nonlocal computational model to study the fluid-structure interaction problem where the fluid is considered to be viscous and weakly compressible and modeled by the PDDO, while the structure is elastic and modeled by the ordinary state-based peridynamics.…”
Section: Introductionmentioning
confidence: 99%
“…13 Yan et al 21,22 further developed a higher order nonlocal operators for the updated Lagrangian particle hydrodynamics and used them to study and simulate multiphase fluid flow problems. Gao and Oterkus 23 developed a nonlocal computational model to study the fluid-structure interaction problem where the fluid is considered to be viscous and weakly compressible and modeled by the PDDO, while the structure is elastic and modeled by the ordinary state-based peridynamics.…”
Section: Introductionmentioning
confidence: 99%
“…PD has been extensively applied to simulate crack growth in a wide range of materials and structures under different loading conditions [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. A limited number of PD formulations for FSI phenomena may be found in the literature, e.g., hydraulic fracturing [26][27][28], ice-water interaction [29], ice-structure interaction [30,31], and fluidelastic structure interaction [32,33]. In our proposed FSI methodology, a stable correspondence-based PD formulation [34] is utilized, which enables direct use of classical continuum material and damage models.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PD can also be applied to subjects other than fracture mechanics (Javili et al, 2019). Many updated mathematical models based on PD theory have been developed over the years: dual-horizon PD was proposed to solve the issue of spurious wave reflections when variable horizons are adopted (Ren et al, 2017); Dual-support SPH was developed in solid within the framework of variational principle (Ren et al, 2019); the PD differential operator provided a differential form for numerical analysis (Gao and Oterkus, 2020); as well as the combination of PD and FEM model (Madenci et al, 2018) and PD least squares minimization (Madenci et al, 2019). Recently, PD was applied to predict ice-structure interaction for a simple structure interaction with ice (Liu et al, 2017;Lu et al, 2018), which showed PD's potential to study ice fracture.…”
mentioning
confidence: 99%